Elevated miR-17-5p facilitates mycobacterial immune evasion by targeting MAP3K2 in macrophages - Jahan, Md Shoykot; Yang, Jinlan; Tang, Yiyue; Xiong, Dehui; Hu, Peilei; Tang, Xichang; Tang, Lijun (Frontiers in Immunology, 2025)
IntroductionTuberculosis (TB) rema\ins a major global health challenge. Mycobacterium avium (M. avium), a non-tuberculosis mycobacterium, causes pulmonary infections and can evade host immune surveillance by persisting within macrophages. MicroRNAs (miRNAs) are key regulators of host immunity; however, their roles in mycobacterial pathogenesis are not fully understood. This study investigated the role of miR-17-5p in macrophage-mediated immune responses during M. avium infection, with a focus on MAP3K2-mediated MAPK signaling.MethodsDifferentially expressed miRNAs were identified through small RNA sequencing of exosomes from M. avium-infected THP-1 macrophages. Candidate miRNAs were validated by RT-qPCR in THP-1 derived exosomes and serum samples from TB patients. MAP3K2 was evaluated as a miR-17-5p target using bioinformatics prediction, dual-luciferase reporter assays, and expression analysis. Effects on immune responses and MAPK signaling were assessed using qPCR, ELISA, Western blotting, ROS measurement, and CFU assays.ResultsmiR-17-5p expression was significantly elevated in M. avium–infected macrophages, as well as in serum and peripheral blood mononuclear cells (PBMCs) from TB patients. Increased miR-17-5p suppressed MAP3K2 expression and attenuated MAPK signaling, reducing phosphorylation of ERK, JNK, and p38. This resulted in decreased production of inflammatory mediators (TNF-α, IL-6, IL-1β), reduced iNOS and ROS levels, and impaired bacterial clearance.DiscussionmiR-17-5p promotes M. avium survival by targeting MAP3K2 and suppressing MAPK-dependent immune functions in macrophages. These findings highlight miR-17-5p as a potential diagnostic biomarker and therapeutic target in TB and related mycobacterial infections.